PENYULUHAN RUMAH SEHAT PADA MASYARAKAT DI KECAMATAN MEDAN KOTA - Sanggam Sihombing; Isniar T. L. Ritonga; Paterson H. P. Sibarani; Darwin Sinabariba (Universitas Methodist Indonesia, 2022)
Community Service (PkM) carried out by the Architecture of the Institute Science and Technology TD. Pardede provided counseling about healthy homes to the community in Medan Kota District. This socialization was held on Thursday, June 9, 2022, at the Medan Kota District Hall in collaboration with the Government Medan Kota by inviting the local community. The method used by providing counseling / lectures and providing an understanding of the importance of a healthy home, then a question and answer is carried out to solve the problems and obstacles faced. The results of PkM with Rumah Sehat counseling are very effective considering that there are still many people who do not understand about healthy houses. With this healthy home counseling, the community understands and the importance of implementing healthy houses in their respective homes so as to create a healthy environment. Keywords: House, Healthy, Medan Kota